Nutrition literacy of technical and higher education students in the countryside of Ceará - Abraão Bruno Lima de Moura; Bruna Yhang da Costa Silva; Davi Moura Lucena; Vitor Lima Mesquita (Demetra, 2020)
Objective: This study aimed to assess the level of nutrition literacy (NL) in technical and higher education students and to compare the level of NL of students in the field of health with that of students in other fields. Methods: A quantitative descriptive and analytical cross-sectional study was carried out from November 2018 to March 2019. The Newest Vital Sign (NVS) translated into Brazilian Portuguese was used to assess the level of literacy. Participants were 289 students, of whom 38.75% were men and 61.25% were women. The participants’ mean age was 22.62 years (SD= 4.55). Results: With regard to the level of literacy, 48.44% of the students presented adequate NL; 25.26% exhibited possibility of limited NL; and 26.30% presented a high probability of limited NL. Adequate levels of NL were found in 70.83% of the students in the field of health and in 41.01% of the students in the other fields. Conclusion: The students had adequate nutrition literacy. Students in the field of health achieved better results when compared with those from other fields.